Development of A Dynamic Network DEA Model To Measure Production Line's Performance: A Conceptual Paper - N. A. M. A., Zainal; Muhamad Arifpin, Mansor; S. N., M. Saffe (2016)
Production line in manufacturing industry usually is made up of several processes and must go through performance measurement to determine whether they are efficient or inefficient. The extended Data Envelopment Analysis (DEA) which is the Network Data Envelopment Analysis (NDEA) is developed to look inside the production line and find the source of inefficiency of each sub process. However, the model can only measure the efficiency of the production line for current time periods only without considering the past time periods and detect any changes of performances that might occur during the time periods. In this paper, we proposed a Dynamic Network DEA model that can be used to measure the performance of the same production line by taking into account any changes according to time. We treat these changes as a Decision Making Units (DMUs) which is the entity that are going to be measured. This dynamic network model only considered the data inputs from different time periods. Our goals of developing the DNDEA model on the production line are to identify the inputs and outputs required and to consider the relationship and connection between each of the processes in the production line and thus measure the performance of the entire production line. The expected outcome of this paper is to propose a conceptual model that can be used for performance measurement in manufacturing production line dynamically.